2019
DOI: 10.1248/bpb.b18-00991
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Extract Modulates Functions of Peroxisome Proliferator-Activated Receptors

Abstract: Cigarette smoke extract (CSE) contains many toxicants and may derange the physiological processes, such as cholesterol metabolism. We examined the impact of CSE on transcriptional regulation mediated peroxisome proliferator-activated receptors (PPARs) and its interaction with cofactors to elucidate differences in the molecular mechanism between CSE and other agonists of PPARs. We constructed several mutant PPARs (mPPARs) with amino acid substitution in the ligand-binding domain, which according to the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…PPARγ is a transcription factor that plays an important role in the regulation of gene expression, formation, and differentiation of adipose tissue [35]. Cigarette smoke extracts affect the transcription of various target genes by binding to PPARγ [36]. A previous study also showed that mice exposed to cigarette smoke for three months had low PPARγ gene expression and protein levels in their alveolar macrophages [37].…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ is a transcription factor that plays an important role in the regulation of gene expression, formation, and differentiation of adipose tissue [35]. Cigarette smoke extracts affect the transcription of various target genes by binding to PPARγ [36]. A previous study also showed that mice exposed to cigarette smoke for three months had low PPARγ gene expression and protein levels in their alveolar macrophages [37].…”
Section: Discussionmentioning
confidence: 99%